P07.30 Impact of expanded screening on the detection of hiv and syphilis in wuxi, china. (13th September 2015) - Meng, XJ; Zou, HC
Abstract : Introduction: HIV and syphilis shares same mode of transmission. In 2010 the Chinese government adopted expanded HIV and syphilis screening strategy (EHSS) across the country in order to timely detect people with these two infections. The impact of this strategy has not been well documented. Methods: HIV and syphilis surveillance data 2004–2014 in Wuxi, China were retrieved. Sources of surveillance data included general hospitals (GHs), sexual health clinics (SHCs), blood donation centres (BDCs), voluntary counselling and testing clinics (VCTs) and others in Wuxi. We used Poisson distribution events test to compare number of HIV and syphilis testing, Chi-squared test to compare HIV and syphilis positive rates and proportions of source of HIV and syphilis notification, between the period before EHSS (Period I, 2004–2009) and the period after EHSS (Period II, 2010–2014). Results: Comparing Periods I and II, 586, 000 vs 1, 423, 000 person-times were screened for both HIV and syphilis (P < 0.001); HIV positive rates were 0.08% (476) vs 0.13% (1, 854) (<0.001); syphilis positive rates were 0.37% (2, 172) vs 0.63% (8, 955) (P < 0.001). In Period I, 18.8%, 10.9%, 7.1%, 14.2% and 49.0% of all HIV positive cases were from GHs, SHCs, BDCs, VCTs and other sources, respectively. This compared to 25.8%, 7.4%, 9.0%, 16.5% and 41.3% in Period II (P < 0.001). In Period I, 42.0%, 13.7%, 7.8%, 1.5% and 35.0% of all syphilis positive cases were from GHs, SHCs, BDCs, VCTs and other sources, respectively. This compared to 26.7%, 28.0%, 17.7%, 1.7% and 25.9% in Period II (P < 0.001). Conclusion: Both the number of HIV and syphilis testing and positive rate increased as a result of EHSS. More HIV infections were detected from GHs compared to syphilis from SHCs in Period II. So HIV-related service capacity building should be enhanced in GHs while that related to syphilis in SHCs in Wuxi, China. Disclosure of interest statement: All authors declare no competing interests.